Rural Adolescent Boys’ Negotiating Romantic Relationships: “We Need to Sacrifice our Brains” - Dmytro, Dana; Luft, Toupey; Jenkins, Melissa; Hoard, Ryan; Cameron, Catherine Ann (Canadian Journal of Counselling and Psychotherapy, 2013)
Twenty-four adolescent boys in Grades 9 to 12 in a rural New Brunswick high school engaged in focussed discussions that were analyzed using grounded theory to determine their heterosexual dating relationship processes. A theory was created from exchange transcriptions. The core category was wrestling with gendered expectations, reflecting their struggle with girls’ and women’s constraints on their relationships. Six related categories elucidated the core category: determining responsibility, keeping it in/letting it out, standing up for oneself, making sacrifices, building trust/not trusting, and showing respect/showing disrespect. Media influences were the contextual conditions. Comparisons with girls’ processes and psycho-educational interventions are considered.